COVID-19 Pandemic, Digital Transformation and the Expansion of Telework - Salavisa, I.; Rebelo, G.; Simões, E. (3rd European Conference on the Impact of Artificial Intelligence and Robotics (ECIAIR 2021), 2021)
The COVID-19 pandemic has dramatically exposed the limits of globalization and the fragility of our societies. On the other hand, it has also accelerated the pace of the digital transformation underway (Schwab, 2016). Notwithstanding the subsequent deep economic crisis, the resilience revealed by the society and the economy owes a lot to a vast range of solutions based in telecommunications and ICT in work organization, services, sales, education and telemedicine. The rapid extension of teleworking represents a major change that is likely to be not fully reversed after the pandemic. In addition to the benefits provided in averting a dramatic blockade (stoppage) of the system, it has also revealed or deepen inequalities among workers, between those who may work from home with adequate access to digital devices and those who cannot. Work-life balance is both a major objective for employees and a big challenge for enterprises. Teleworking may contribute to this balance. It occupies a central place in EU social policies, especially related with the working environment and organization associated with work-life balance, health, performance and workers' perspectives (Eurofound, 2020). In this paper, we will address theoretically and empirically the extension of teleworking and its socioeconomic, legal, and ethical impacts in advanced countries, with a particular focus on the Portuguese case. We will draw on official data and recent surveys carried out by the European Commission agencies, the OECD, the Portuguese Statistical Office, and other entities, such as research institutions, international consultancy companies and employers’ organizations. We will also analyze the return to face-to-face activity after many workers have experienced the flexibility of working from home. These changes may strongly influence the shape of work organization and labour markets landscape in the short-term an in the future and affect society and economy as a whole (Huws, 2017; ILO, 2020).